Seasonal agricultural workers and the habitus of mobile precarity. (14th May 2019) - Jackson, Samantha
This article uses habitus as a tool to unpack the transnational experience of workers who move between Canada and home through the Seasonal Agricultural Worker Program (SAWP). Through disciplining regulations and annual forced exits, the SAWP engenders a particular form of transnationalism that is marked by precarity but also efforts to subversively carve out space at home and abroad. Habitus provides a unifying theory to understand workers' experiences while also locating the SAWP within broader systems of exclusion. This article moves in three parts: first, transnationalism and habitus are examined as tools to explore the experiences of SAWP workers. Then, the SAWP policy context is reviewed. It concludes with an analysis of migrant workers' renegotiations of the boundaries of habitus through subversive acts of citizenship.